2005
DOI: 10.1063/1.2141649
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile phase change memory nanocell fabrication by femtosecond laser writing assisted with near-field optical microscopy

Abstract: The phase change memory cells were developed by using a combination system of a femtosecond laser with near-field scanning optical microscopy. The memory cells with feature size varying from 800nm down to 90nm were achieved. The cell functional performances were tested, and the scalability of the programming current as a function of the memory cell features was investigated. The optical near-field distance which is one of the critical factors to achieve high resolution nanostructures was studied experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…As reported in many previous works using the GST alloy232425262728, GST undergoes a phase change which can be repetitively switched. Because the material characteristics of GST can differ slightly when different composition ratios and sputtering conditions are used23, it was necessary to measure the electrical resistances and optical constants of the actual GST alloy used in this work for amorphous and crystalline states.…”
Section: Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…As reported in many previous works using the GST alloy232425262728, GST undergoes a phase change which can be repetitively switched. Because the material characteristics of GST can differ slightly when different composition ratios and sputtering conditions are used23, it was necessary to measure the electrical resistances and optical constants of the actual GST alloy used in this work for amorphous and crystalline states.…”
Section: Methodsmentioning
confidence: 72%
“…Between amorphous and crystalline states, significant changes in the refractive index and extinction coefficients which reach nearly ~0.5 at visible frequencies have been reported24. Moreover, the phase change of GST film is non-volatile, repetitive, and easily controlled by both electric and photonic stimuli25. Therefore, it has been reported that only a few nanometers of GST film can result in a total change of the reflected color, with the inserting of the GST film into the dielectric cavity24.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The switch can be turned back ON by heating the PC layer to the crystallization temperature and by slowly removing the heat. The transition temperature can be reached by employing hot probes in contact with the PC material [8], using lasers [9], or passing current either through the PC material itself (direct heating) [10], or through a separate heater layer adjacent to the PC layer (indirect heating) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the methods of cell structure engineering [3][4][5] and material engineering [6], smaller programming currents can be achieved simply through cell size minimization [3][4][5][7][8]. Followed by 180 nm PCRAM fabrication by Intel [9] in 2001, various advanced lithography technologies such as Electron Beam [10] and Near-field Optical Microscopy (NSOM) [11] have been used to fabricate PCRAM cells less than 50 nm.…”
Section: Introductionmentioning
confidence: 99%